Myth and magic in heavy metal music - McParland, Robert (McFarland & Company, 2018)
"Myth pervades heavy metal. With visual elements drawn from medieval and horror cinema, the genre's themes of chaos, dissidence and alienation transmit an image of Promethean rebellion against the conventional. The author explores the music of Black Sabbath, Iron Maiden, Judas Priest, Metallica and many others from a mythological and literary perspective"--